Cardiovascular drug interventions in the cardio-oncology clinic by a cardiology pharmacist: ICOP-Pharm study - Yaseen, Israa Fadhil; Farhan, Hasan Ali (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardio-oncology is a rapidly growing field that requires a novel service design to deal with the increasing number of patients. It is reported that the volume of the patients at the cardio-oncology clinic in UK is (535 patients/ 5 years) and in Canada is (779 patients/ 7 years). The pharmacist has a role in reducing the consultation time of physicians. Objective: To identify the role of a qualified cardiology pharmacist at the cardio-oncology clinic using a new paradigm based on complementary interventions with the cardiologist for the management of patients with cancer and cardiovascular risk factors and/or cardiovascular diseases (CVRF/CVD). Methods: A prospective observational study was conducted at the cardio-oncology clinic in the Medical City in Baghdad/Iraq between December 2020 - December 2021. Patients with CVRF/CVD were registered. ICOP-Pharm paradigm was designed to involve a qualified cardiology pharmacist for initial cardiovascular (CV) drug interventions. Results: Among 333 patients who attended our clinic over the one-year interval, 200 (60%) CVRF/CVD cases were enrolled in the study, and from them 79 (40%) patients had CV drug interventions. A total of 196 interventions were done, including 147 (75%) performed by the cardiology pharmacist, and 92 (63%) of the latter were CV drug initiation mainly in patients with hypertension 32 (26%), followed by cancer therapy-related cardiac dysfunction 29 (24%). Conclusions: The qualified cardiology pharmacist was responsible for three-quarters of initial CV drug interventions at the cardio-oncology clinic in a complementary approach to the cardiologist. The role of the cardiology pharmacist in the ICOP-Pharm paradigm may be one of the reasons for the ability of the heart team to manage three-fold of the patients’ volume when compared with those in the UK or Canada.